New detection method of SARS-CoV-2 antibodies toward a point-of-care biosensor - Nelson-Mora, Janikua; Rubio, Diana; Ventura-Martínez, Amairani; González, Luis A.; Del-Rio, Diana; Aranda-López, Yuli; Jiménez-Díaz, Edgar; Zamarrón-Hernández, Diego; Ríos-López, Diana G.; Aguirre, Stephanie; Ruiz-Hernandez, Yasab; Cruz-Ramírez, Aarón; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
The outbreak of COVID-19, a disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, is regarded as the most severe of the documented coronavirus pandemics. The measurement and monitoring of SARS-CoV-2 antibody levels by serological tests are relevant for a better epidemiological and clinical understanding of COVID-19. The aim of this work was to design a method called the SARS-CoV-2 antibody detection method (SARS-CoV-2 AbDM) for fluorescence immunodetection of anti-SARS-CoV-2 IgG and IgM on both plate and microfluidic chip. For this purpose, a system with magnetic beads that immobilize the antigen (S protein and RBD) on its surface was used to determine the presence and quantity of antibodies in a sample in a single reaction. The SARS-CoV-2 AbDM led to several advantages in the performance of the tests, such as reduced cost, possibility of performing isolated or multiple samples, potential of multiplex detection, and capacity to detect whole blood samples without losing resolution. In addition, due to the microfluidic chip in conjunction with the motorized actuated platform, the time, sample quantity, and operator intervention during the process were reduced. All these advantages suggest that the SARS-CoV-2 AbDM has the potential to be developed as a PoC that can be used as a tool for seroprevalence monitoring, allowing a better understanding of the epidemiological and clinical characteristics of COVID-19 and contributing to more effective and ethical decision-making in strategies to fight against the COVID-19 pandemic.